The Relationship of Feed Consumption And Body Condition Score With Ovarian Hypofunction In Cattle Pesawaran District: The Relationship of Feed Consumption And Body Condition Score With Ovarian Hypofunction In Cattle - Khairul Akmal; Enny Tantini Setiatin; Anis Muktiani (Universitas Djuanda, 2026)
Cases of ovarian hypofunction in beef cattle on smallholder farms greatly influence livestock reproductive activities, especially to achieve successful pregnancy in cattle with reproductive disorders. The material used in this research was 88 cattle belonging to breeders in Pesawaran Regency which were taken using the criteria of cattle having ovarian hypofunction reproductive disorders with a census of 68 breeders as respondents. Primary data was obtained directly in the field through interviews with each beef cattle farmer, while secondary data was obtained from related agencies. The results of research on feed consumption (X1) and Body Condition Score (X2) simultaneously have a very significant effect on the rate of recovery from hypofunction (Y). The partial T test of the feed consumption variable (X1) had no effect on the recovery rate, as shown by the significance value of 0.562 > 0.05. Meanwhile, Body Condition Score (X2) had a very significant effect on the recovery rate (Y). Meanwhile, the Body Condition Score variable (X2) has a very real influence on the recovery rate, as indicated by the significance value of 0.000<0.0. The research can be concluded that feed consumption and Body Condition Score have a relationship with the level of recovery from hypofunction